Long-term efficacy of catheter ablation for atrial fibrillation: impact of additional targeting of fractionated electrograms. Issue 17 (18th May 2010) - Hunter, R J; Berriman, T J; Diab, I; Baker, V; Finlay, M; Richmond, L; Duncan, E; Kamdar, R; Thomas, G; Abrams, D; Dhinoja, M; Sporton, S; et al.
Abstract : Objectives: To investigate long-term efficacy of catheter ablation for atrial fibrillation (AF) and the impact of ablating complex or fractionated electrograms (CFEs) in addition to pulmonary vein isolation and linear lesions in persistent AF (PeAF). Methods: Consecutive cases from 2002–2007 were analysed. All the patients underwent a wide-area circumferential ablation with confirmation of electrical isolation. For PeAF, linear lesions were added, with additional targeting of CFE from 2005. Data were collected in a prospective database. Attempts were made to contact all patients for follow-up. Results: 285 patients underwent 530 procedures. The mean (SD) age was 57 (11) years, 75% were male, 20% had structural heart disease and 53% had paroxysmal AF (PAF). The mean number of procedures was 1.9 per patient (1.7 for PAF and 2.0 for PeAF). Procedural complications included stroke or transient ischemic attack in 0.6% and pericardial effusion requiring drainage in 1.7%. During 2.7 years (0.2 to 7.4 years) of follow-up from the last procedure, there were seven deaths (unrelated to their ablation or AF) and three strokes or transient ischemic attack (0.3% per year). Freedom from AF/atrial tachyarrhythmia was 86% for PAF and 68% for PeAF. Late recurrence was 3 per 100 years of follow-up after >3 years. The Kaplan–Meier analysis showed that CFE ablation improved the outcome for PeAF after the first cluster of procedures (p=0.049), with a trend towards improved final outcome (p=0.130). Conclusions: Long-term freedom from AF is achievable in most patients with PAF and PeAF with low rates of late recurrence. Additional targeting of CFE improves outcome for PeAF. Late adverse events including stroke are few.